The complete chloroplast genome sequence of Michelia xinningia (Magnoliaceae) - Nawaz Haider Bashir; Muhammad Naeem; Zijie Wang; Yong Gao (Mitochondrial DNA. Part B. Resources)
Michelia xinningia is an evergreen garden plant with attractive and fragrant flowers. Michelia exhibits both interspecific and intraspecific phenotypic variability. However, the genetic diversity of M. xinningia has not been thoroughly investigated. This study analyzed the first chloroplast genome of M. xinningia, which was 160,082 bp, including a large single-copy (LSC) region of 88,112 bp, a small single-copy (SSC) region of 18,798 bp, and a pair of inverted repeat (IRs) regions of 26,586 bp. It contained 133 genes, including 87 protein-coding genes, 38 transfer RNA genes, and eight ribosomal RNA genes. Phylogenetic analysis showed that M. xinningia formed a close relationship with M. foveolata. This study will provide an opportunity to investigate genetic variation and could be useful for both species identification and conservation.